Damage-controlled allowable maximum stress of the stirrup for HSRC beam members based on lower-bound theory. (October 2022) - Chiu, Chien-Kuo; Liao, I-Hsiang; Putra, Muhammad Dachreza Tri Kurnia
Abstract: The main purpose of this work is to investigate the damage-controlled allowable maximum stress of the stirrup of a high-strength reinforced concrete (HSRC) beam member in the general design using the lower-bound theory. Since several works have noted that the allowable stress of the stirrup of an RC beam in the general design is limited by the shear crack width, the relationship between shear crack width and applied shear force is obtained herein using available experimental data for HSRC beam members. Moreover, based on the fact that the allowable maximum shear crack widths that have been suggested elsewhere are related to the damage state, formulas for estimating the allowable maximum stress of the stirrup of an HSRC beam member with various specified compressive strengths of concrete and stirrup ratios are provided herein. Restated, the allowable maximum stress of the stirrup can be determined from the specified compressive strength of the concrete and the stirrup ratio.